Congenital left hemidiaphragmatic agenesis : A case report - Wijaya, William; Yustinus Rurie Wirawan (ARKA INSTITUTE, 2022)
Congenital diaphragmatic hernia is a congenital diaphragmatic disorder characterized by herniation of the abdominal viscera into the thoracic cavity. In rare diaphragmatic developmental abnormality cases, there is complete diaphragmatic agenesis. This study aims to report a case of left hemidiaphragmatic agenesis with a typical postnatal course of the disease. The research method used is descriptive qualitative. The results showed that a 13-day-old baby girl experienced respiratory problems for a week. Chest radiography showed left-sided congenital diaphragmatic hernia. It can be concluded that left diaphragmatic agenesis is a rare developmental disorder of the diaphragm. Surgical intervention as early as possible can prove beneficial for the patient. Patients can be treated surgically without using prosthetic materials by mobilizing and suturing the remaining diaphragm with the intercostal muscles.